Financial toxicity in sarcoma patients and survivors in Germany: results from the multicenter PROSa study - Büttner, Matthias; Singer, Susanne; Hentschel, Leopold; Richter, Stephan; Hohenberger, Peter; Kasper, Bernd; Andreou, Dimosthenis; Pink, Daniel; Taylor, Kathy; Arndt, Karin; Bornhäuser, Martin; Schmitt, Jochen; et al. (Supportive care in cancer, 2022)
Cancer patients have been shown to frequently suffer from financial burden before, during, and after treatment. However, the financial toxicity of patients with sarcoma has seldom been assessed. Therefore, the aim of this study was to evaluate whether financial toxicity is a problem for sarcoma patients in Germany and identify associated risk factors.